Associated Properties of γ-π gγ-closed Functions - O. Ravi; S. Margaret Parimalam; S. Murugesan; A. Pandi (International Journal of Mathematics And its Applications, 2015)
The concept of γ-open sets was introduced in [3,7,11]. The primary purpose of this paper is to introduce and study pre-π gγ-closed functions by using γ-open sets.